(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article deeply studies the issue of developing general cultural competencies of students of general secondary schools through hadiths. The content and essence of hadiths, their educational and educational potential, and methods of applying them to the modern pedagogical process are widely covered. During the research, the role of hadiths in instilling moral values, increasing social responsibility, forming intercultural dialogue, and developing personal qualities was analyzed. Practical observations have shown that lessons organized on the basis of hadiths are an effective tool for developing moral education, tolerance, mutual respect, independent thinking, and social activity in students. Also, hadiths form such qualities as loyalty to national and universal values, respect for parents and teachers, honesty, and hard work in the younger generation. The results of pedagogical experiments confirmed that it is possible to improve the general cultural level of students by combining hadiths with modern pedagogical approaches.